PIM-DL: Expanding the Applicability of Commodity DRAM-PIMs for Deep Learning via Algorithm-System Co-Optimization - Li, Cong; Zhou, Zhe; Wang, Yang; Yang, Fan; Cao, Ting; Yang, Mao; Liang, Yun; Sun, Guangyu (29th ACM International Conference on Architectural Support for Programming Languages and Operating Systems (ASPLOS'24), 2024)
DRAM-based processing-in-memory (DRAM-PIM) has gained commercial prominence in recent years. However, their integration for deep learning acceleration poses inherent challenges. Existing DRAM-PIMs are limited in computational capabilities, primarily applicable for element-wise and GEMV operators. Unfortunately, these operators contribute only a small portion of the execution time in most DNN workloads. Current systems still necessitate powerful hosts to handle a significant portion of compute-heavy operators. To expand the applicability of commodity DRAM-PIMs in accelerating deep learning, we introduce a novel PIM-DL framework. The philosophy behind PIM-DL is to replace the compute-heavy GEMM operations in linear layers with Lookup-Tables (LUTs). Such LUT-based neural networks (LUT-NNs) substantially reduce multiplications in DNN inference, rendering them suitable for efficient execution on DRAM-PIMs. To accurately convert DNNs into LUT-NNs and achieve optimal inference serving performance, we first introduce an enhanced LUT-NN (eLUT-NN) algorithm for model calibration, then we propose an Auto-Tuner capable of optimizing the mapping parameters on diverse DRAM-PIM platforms. We evaluate PIM-DL on off-the-shelf UPMEM PIM-DIMM products and simulated HBM-PIM/AiM platforms across multiple contemporary DNN workloads. Compared with GEMM-based inference on DRAM-PIMs, PIM-DL achieves 22.6× 37.1× speedup. Compared with CPU/GPU-based inference, PIM-DL achieves up to 3.54×/1.20× speedup